“Klio-72” as a personalization of intergenerational memory in Yu.V. Trifonov’s novel “Impatience” - Sergeeva, Elena N.; Sundukova, Kseniya A. (Semiotic studies, 2025)
In the narrative structure of the novel “Impatience”, dedicated to the “People’s Will” organization, the Soviet writer Yu.V. Trifonov reflects the dynamics of intergenerational memory and oblivion, described later by the researcher of memorial history Aleida Assman through the categories of “archive”, “selective memory”, “obsolescence”, etc. The main part of the novel is a reflection of the consciousness of Andrei Zhelyabov, but the text also contains evidence about him from other characters, written in the first person and designated as “Voices”, attributed to other time layers. A more unexpected narrative authority is introduced in the chapters of “Klio-72”, where the voice of history is heard. Both the voices of contemporaries and “Klio-72” in the artistic world of the novel cannot be identified with the document, have their own subjectivity and enter into polemics with each other and with the position of the hero. This polemic and the complex artistic meaning it creates will be the subject of our attention in this article.